Diseño y simulación de una máquina trilladora de arroz que sea factible para el pequeño agricultor, en el Cantón Quevedo, Provincia de los Ríos - Triviño Veloz, Harli Nexar (2016)
The present investigation aimed to design a threshing machine whose function is to separate the rice grain from the spike, in order to optimize the time, quality and technification of the threshing process that is currently carried out manually by the Quevedo farmers. The methods used have been deductive, analytical and inductive whose research instruments such as surveys and observation to determine conditions and parameters related to the threshing process. As results were obtained that 40% of the farmers use from 4 to 6 hectares for the rice crop, which according to 60% of respondents use Type SFL 09 (long grain) and whose time is more than 6 hours (manual threshing). As for the design and simulation of the rice threshing machine were established that the St34 material should be used while the St42 material was required for the shaft and with respect to power the value of 1.5 HP and a speed of 12 m / s for the A-belt. Regarding the financial study, it was determined that the farmer would be doubling his profit by acquiring a threshing machine at $ 24,023.13 over a 5-year period. Likewise, if a farmer continues his activities without a rice threshing machine, they would have a NPV of $ 10,131.68 while if he acquires the NPV it would amount to $ 18,423.38 with a TIR of 140.89% which means that it is economically feasible for the farmer to acquire this machinery for the use of threshing of his harvest. Finally, the manual of operations and maintenance is presented which is classified in seven key aspects related to the training that the operator must have to operate the machine, guidelines for safe operation, safety labels. In addition, Threshing machine and its main parts, checking and precautions Operation, and replacement of parts in order to allow farmers to have a clear idea of the operation of a threshing machine.